Linguo-didactic bases of foreign students’ intercultural communication competencies formation in studying the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Increasing the number of foreign students in Ukrainian high educational institutions has promoted the development of methods of teaching Ukrainian as a foreign language. For this purpose “The concept of language training for foreign students in Ukrainian high educational institutions“ has been developed. It has been defined that the aim of language training of foreign citizens is to meet the demand of communication in different areas, such as scientific, socio-political, socio-cultural, colloquial; harmonious development of personality capable to the intercultural dialogue. A lot of textbooks and teaching aids were published. But the issues of development of methods and techniques of teaching Ukrainian as a foreign language, their adaptation to the changing life conditions are still topical.The analysis of scientific literature shows that extralinguistic, system, communicative, functional, person-centered, complex, competency-based, cultural approaches are applied to the development of intercultural communication of foreign students. Among the didactic principles scientists identify the principles of awareness, sequence, accessibility, systematic and consistency, demonstrativeness, combination theory with practice. Direct, audio-lingual, practical, communicative, read methods are used for the realization of goals, objectives and content of education. According to the above principles and methods of teaching foreign students Ukrainian the following exercises such as communicative, conditional-communicative and non-communicative are divided. At the same time to develop foreign students’ intercultural communication competencies the exercises aimed at intercultural awareness and perception improvement, culture comparison, communicative competence formation in intercultural situations are used.
Keywords: Ukrainian as a foreign language; foreign students; educational approaches; teaching methods; intercultural communication competencies